Association of the Serotonin and Kynurenine Pathways as Possible Therapeutic Targets to Modulate Pain in Patients with Fibromyalgia - Alfonso Alfaro-Rodríguez; Samuel Reyes-Long; Ernesto Roldan-Valadez; Maykel González-Torres; Herlinda Bonilla-Jaime; Cindy Bandala; Alberto Avila-Luna; Antonio Bueno-Nava; Elizabeth Cabrera-Ruiz; Pedro Sanchez-Aparicio; Angélica González Maciel; Ana Lilia Dotor-Llerena; et al. (MDPI AG, 2024)
Fibromyalgia (FM) is a disorder characterized by widespread chronic pain, significant depression, and various neural abnormalities. Recent research suggests a reciprocal exacerbation mechanism between chronic pain and depression. In patients with FM, dysregulation of tryptophan (Trp) metabolism has been identified. Trp, an essential amino acid, serves as a precursor to serotonin (5-HT), a neuromodulator that influences mood, appetite, sleep, and pain perception through the receptors 5-HT1, 5-HT2, and 5-HT3. Additionally, Trp is involved in the kynurenine pathway, a critical route in the immune response, inflammation, and production of neuroactive substances and nicotinamide adenine dinucleotide (NAD+). The activation of this pathway by pro-inflammatory cytokines, such as tumor necrosis factor α (TNF-α) and interferon gamma (IFN-γ), leads to the production of kynurenic acid (KYNA), which has neuroprotective properties, and quinolinic acid (QA), which is neurotoxic. These findings underscore the crucial balance between Trp metabolism, 5-HT, and kynurenine, where an imbalance can contribute to the dual burden of pain and depression in patients with FM. This review proposes a novel therapeutic approach for FM pain management, focusing on inhibiting QA synthesis while co-administering selective serotonin reuptake inhibitors to potentially increase KYNA levels, thus dampening pain perception and improving patient outcomes.